KEPASTIAN HUKUM PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) TERKAIT PENENTUAN HARGA OLEH BADAN PENGELOLA KEUANGAN DAERAH (BPKD) DIATAS NILAI TRANSAKSI JUAL BELI - Heri Sutikno; Khalimi, Khalimi; Felicitas Sri Marniati (Bajang Institute, 2025)
Transaction value as certainty of buying and selling transactions. Land and Building Rights Acquisition Fee as Proof of Regional Tax Payment. BPHTB Tax Collection Procedures must be in accordance with the Legislative Regulations and regulations under them so that the determination of prices related to BPHTB tax by the Regional Financial Management Agency (BPKD) is in accordance with existing regulations. The transaction value in a sale and purchase transaction of land and buildings is one of the transfers of land rights, therefore how the implementation of BPHTB collection is related to price determination by BPKD for the sale and purchase value and what is the legal certainty of BPHTB collection above the sale and purchase value. The theories used in this research are the Theory of Service or Absolute Obligation from Mardiasmo and the Theory of Legal Certainty from Gustav Redbruch.The method used in this research is a type of normative juridical research, namely legal library research or secondary data with primary, secondary and tertiary sources of legal materials. The research approaches used are the Legislative Approach, Case Approach, Analytical Approach, Conceptual Approach and legal material collection techniques are carried out by identifying and inventorying positive legal rules, book literature, journals and other legal material sources. The analysis technique for legal materials is carried out using grammatical, systematic legal interpretation, and methods of analogous legal construction and legal refinement.From the research results, it can be seen that in the price determination collection by the Regional Financial Management Agency (BPKD) in determining the value of buying and selling transactions, it is based on the currently applicable Regional Laws and Regulations, while the Regent's regulations regarding Land Value Zone Estimates in the imposition of BPHTB in determining Transaction Values, these regulations serve as a comparison in the data verification process in the field.